Design, Analysis and Performance Evaluation of Electrical Power Subsystem based on Triple-Junctions Solar PV Cells and SEPIC for a Conceptual 1u Cubesat Mission - Danladi, Ali; KurtoÄŸlu, Mehmet; Vural, Ahmet Mete (EMITTER International Journal of Engineering Technology, 2019)
This study aims to popularize low voltage power supply design especially for space satellite Cubesat mission and other portable consumer electronic devices. In this context, a preliminary design of an electrical power subsystem (EPS) is carried out for a conceptual 1u Cubesat mission in this paper. Mathematical modeling of the basic elements of the EPS is presented. Photovoltaic (PV) power generation system that is selected is made up of triple-junction solar cells, and the battery charging system based on lithium technology as well as the power conditioning converters are selected based on single ended primary inductance converter topology popularly abbreviated as SEPIC. Triple-junction solar PV cell results are verified by comparing with the datasheet values. A maximum power point tracking algorithm which is known as perturb and observe is implemented and proportional-integral controller is used for the SEPIC. All of these are well analyzed, mathematically modeled and simulated. Feasibility of the designed EPS is verified by comparing with similar devices from different manufacturers.